Qualitative determination of indole alkaloids, triterpenoids and steroid of Tabernaemontana hilariana - Cardoso, CAL; Vilegas, Wagner [UNESP]; Honda, N. K. (Elsevier B.V., 1998)
This paper reports the separation and identification of indole alkaloids, steroids and triterpenoids from the ethanolic extracts of Tabernaemontana hilariana (Apocynaceae). The alkaloidal fractions from the ethanolic extracts obtained (root barks, green fruits, ripe fruits and seeds) were fractionated and analysed by thin-layer chromatography, capillary gas chromatography-flame ionization detection (cGC-FID) as well as by high-resolution gas chromatography-mass spectrometry (HRGC-MS). 3-Hydroxycoronaridine, ibogamine, coronaridine pseudoindoxyl, coronaridine, catharanthine, voacangine hydroxyindolenine, voacangine pseudoindoxyl, tabernanthine, tetraphyllicine, 3-hydroxyvoacangine, voacangine, isovoacangine and 3-oxocoronaridine were identified. The insoluble fraction of ethanolic extracts obtained from the root barks and green fruits were analysed and ten aliphatic constituents were also identified by cGC-FID and HRGC-MS. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: Tabernaemontana hilariana; plant materials; indoles; alkaloids; triterpenoids; steroids